A Qualitative Examination of Withdrawing Sexual Consent, Sexual Compliance, and Young Women's Role as Sexual Gatekeepers. Issue 4 (2nd October 2022) - Benoit, Aryn A.; Ronis, Scott T.
Abstract: Introduction: Withdrawing consent for sex may be difficult for young women due to gendered sexual scripts and male persistence. Method: 40 students from Canadian universities (31 women; Mean age = 20.20 years; 75% heterosexual) were asked open-ended questions about sexual experiences and consent; data were analyzed using thematic analysis. Results: Women perceived that: (1) women were responsible for communicating consent, (2) they were unaware it was acceptable to withdraw consent or did not know how to, (3) male partners often persisted in response to withdrawal of consent, and (4) these experiences factored into compliance. Conclusion: Sexual consent education, at least in North America, should increase emphasis on withdrawing consent.